Localized Population, Habitat Predictors, and Threats of Cheer Pheasant, in Pyuthan District, Nepal (Journal of Forest and Natural Resource Management, 2025)
This study assessed the population density, habitat preferences, and conservation threats to the globally vulnerable Cheer Pheasant (Catreus wallichii) in the Pyuthan District. Dawn Call Count surveys were conducted at 16 stations. Habitat variables were measured within 300-meter radii of each station. A Generalized Linear Model analyzed habitat preferences, while semi-structured questionnaires assessed conservation threats and local perceptions. The study recorded a population density of 6 birds/km² with a detection rate of 1.12 birds per station, concentrated in the Lahare Vir block. Habitat analysis revealed significant preferences for areas with moderate fire damage (p=0.032), proximity to settlements (p=0.025), and low shrub density (p=0.009). Hunting emerged as the primary threat (44%), followed by forest fires (18%), habitat degradation from overgrazing (12%), lack of awareness (12%), and predators (14%). While 94% of locals were unaware of the species' protected status, 78% expressed support for its conservation. This study establishes baseline population data for Cheer Pheasant in Pyuthan district and identifies critical habitat preferences, contributing to our understanding of the species' ecology in non-protected areas. The findings suggest the need for integrated conservation strategies that combine habitat management through controlled burning, community-based conservation initiatives, and enhanced law enforcement against hunting.